Pengaruh Konsentrasi Ekstrak Daun Sirsak Terhadap Penurunan Kualitas Telur Ayam Ras Selama Penyimpanan - Isye Jean Liur (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
Hen egg is easy to get and affordable. Besides having a complete nutritional content, chicken eggs are also easily damaged due to microbial activity during storage so that it can reduce egg quality. Therefore, a preservation process is needed to maintain egg quality. This study aims to determine the effect of soursop leaf extract concentrations on decreasing the quality of eggs. This research used a completely randomized design with two factors, the first factor was the concentration of soursop leaf extract (20, 30, 40%) and the second was the shelf life (0, 7, 14, 21 and 28 days). Observation included egg white index, egg yolk index, haugh unit, and weights of eggs. The results indicate that eggs with soursop leaf extract immersion treatment can maintain egg quality. The concentration of soursop leaf extract as much as 40% gives better results in maintaining the quality of eggs.